Review of Becoming a library leader - Rachel Evans (Journal of New Librarianship, 2020)
Review of Freedman, James M. and Freedman, Shin (Ed.) (2020). Becoming a library leader: Seven stages of leadership development for academic librarians. Chicago: Association of College and Research Libraries.